2014
DOI: 10.1080/00223131.2014.921581
|View full text |Cite
|
Sign up to set email alerts
|

Early construction and operation of the highly contaminated water treatment system in Fukushima Daiichi Nuclear Power Station (IV) - Assessment of hydrogen behavior in stored Cs adsorption vessel

Abstract: Hydrogen diffusion behavior in a cesium adsorption vessel is assessed. The vessel is used to remove radioactive substance from contaminated water, which is proceeded from Fukushima accident. Experiment and numerical calculation are conducted to clarify the characteristics of natural circulation in the vessel. The natural circulation arising from the temperature difference between inside and outside the vessel is confirmed. We develop an evaluation model to predict the natural circulation and its prediction agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Zeolites are crystalline aluminosilicates that have nanometer-scale porous frameworks and exchangeable cations in extraframework positions. The radiolysis of zeolite/water systems also has a specific importance in the application of zeolites as ion-exchange adsorbents in treating radioactively contaminated water. During the treatment and storage of spent zeolite adsorbents, it has been found that after the treatment water radiolysis produces H 2 . Appropriate estimation and control of H 2 are indispensable for the safe operation of the treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolites are crystalline aluminosilicates that have nanometer-scale porous frameworks and exchangeable cations in extraframework positions. The radiolysis of zeolite/water systems also has a specific importance in the application of zeolites as ion-exchange adsorbents in treating radioactively contaminated water. During the treatment and storage of spent zeolite adsorbents, it has been found that after the treatment water radiolysis produces H 2 . Appropriate estimation and control of H 2 are indispensable for the safe operation of the treatment process.…”
Section: Introductionmentioning
confidence: 99%